Microcystic Stromal Tumor of the Ovary With Mutation in Exon 3 of β-catenin: A Case Report. (March 2015) - Kang, Yu Na; Cho, Chi Heum; Kwon, Sun Young
Abstract : Microcystic stromal tumor of the ovary is a very rare ovarian tumor with distinctive microcystic histologic features and a characteristic immunophenotype of stromal tumor. However, its origin, tumor pathogenesis, and prognosis have not been well established until now. We report a very unusual case of a microcystic stromal tumor of the ovary with a mutation in exon 3 of the β-catenin ( CTNNB1 ) gene. Macroscopically, the fragmented ovarian tumor showed a diffuse solid mass. Microscopically, the tumor had a pathognomonic histologic pattern of solid and cellular areas with microcysts and fibrous hyalinized stroma. Immunohistochemical staining with CD10, vimentin, CD99, and β-catenin showed positive expression. However, α-inhibin and E-cadherin showed negativity. Mutational analysis revealed a point mutation in exon 3 of the β-catenin ( CTNNB1 ) gene.